Shari'ah Non-compliance Risk Management and Legal Documentations in Islamic Finance Documentations in Islamic Finance - Lahsasna, Ahcene (Wiley Finance, 2014)
A comprehensive guide to one of the key risk management issues in the expanding field of Islamic finance For Islamic financial institutions, Sharia non-compliance is a growing and key risk that must be carefully managed. This book offers a thorough look at non-compliance risk and explains the legal documentation necessary to ensure compliance for professionals in the Islamic finance industry. In addition, the book offers helpful guidance and understanding for the legal departments of Islamic financial institutions, as well as lawyers, legal firms, Shariah advisors, Shariah officers, and students studying Islamic finance. The book covers fundamental concepts, major risk elements, tools and techniques for identifying non-compliance, legal documentation, and the impact of non-compliance, among other vital topics. Offers comprehensive coverage of the growing field of non-compliance risk management in Islamic finance Includes in-depth coverage of legal documentation Written by an expert on the topic who teaches at INCEIF, The Global University for Islamic Finance and IIUM, International Islamic University of Malaysia in Malaysia